2006
DOI: 10.1152/ajpheart.00455.2005
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of remote microvascular preconditioning requires KATP channel activity

Abstract: The purpose of this study was to investigate vascular preconditioning of individual microvascular networks. Prior work shows that exposure of downstream arterioles to specific agonists preconditions upstream arterioles so that they exhibit an altered local vasoactive response [remote microvascular preconditioning (RMP)]. We hypothesized that mitochondrial ATP-sensitive K+ (K(ATP)) channels were involved in stimulation of RMP. Arteriolar diameter (approximately 15 microm) was observed approximately 1,000 microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
(70 reference statements)
3
22
0
Order By: Relevance
“…Thus, the exposure time of the GNP-Dex was extended to 30 seconds. Finally, testing the range of concentrations is critical since it is well known that long-lasting pro-inflammatory responses can be induced if inflammatory agents are exposed to the vasculature even briefly (seconds)474849505152. The exposure to GNP-Dex to the terminal or arcade arterioles caused a dose dependent dilation and yielded statistically similar EC 50 (half of maximal dilation observed, noted on Figure 7B) and maximal dilation values in both.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, the exposure time of the GNP-Dex was extended to 30 seconds. Finally, testing the range of concentrations is critical since it is well known that long-lasting pro-inflammatory responses can be induced if inflammatory agents are exposed to the vasculature even briefly (seconds)474849505152. The exposure to GNP-Dex to the terminal or arcade arterioles caused a dose dependent dilation and yielded statistically similar EC 50 (half of maximal dilation observed, noted on Figure 7B) and maximal dilation values in both.…”
Section: Discussionmentioning
confidence: 85%
“…Male hamsters (100 ± 4 days, mean ± SD, 112.5 ± 10 grams, n = 8) were anesthetized with isoflurane (4% induction, 1% thereafter). The left cheek pouch tissue was exteriorized, pinned across a Lucite pedestal and cleared of connective tissue48515255. Physiological saline flowed over the exteriorized tissue (5 ml/min).…”
Section: Methodsmentioning
confidence: 99%
“…In the hamster, the left cheek pouch tissue was prepared, as previously. (Frame and Mabanta, 2007, Frame et al, 2007, Mabanta et al, 2006, Mustafa et al, 1999) In the mouse, the right cremaster muscle was prepared, as previously. (Georgi et al, 2011b) For each, the tissue was pinned across a quartz pedestal with warmed superfusate (physiological saline) flowing over the flat tissue at a rate of 5 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…Dickson et al showed blockade of K ATP channels abolished transferred preconditioning in virgin hearts conferred by coronary effluent from preconditioned hearts [66]. Mabanta et al showed that remote microvascular preconditioning is mediated by K ATP channels and blockade of K ATP channels abolished preconditioning [129]. Pell et al showed renal IR (10 min cycles) reduced myocardial infarct size and cardioprotection was abolished by K ATP blockers (5-HD) [27].…”
Section: Evidencementioning
confidence: 99%